Corporate governance and Islamic bank accountability based on disclosure—a study on Islamic banks in Indonesia - Hasan Mukhibad; Prabowo Yudo Jayanto; Trisni Suryarini; Bayu Bagas Hapsoro (Cogent Business & Management, 2022)
Shariah principles used as the primary basis for bank operations emphasize information disclosure as manager accountability to stakeholders. This form of accountability can be presented by presenting broader information disclosure, i.e., the disclosure of information on social, finance, and shariah compliance performance. We expand the disclosure, which is not limited to the disclosure of Corporate Social Responsibility (CSR). This study aims to examine the effect of the Board of Directors (BOD) and Shariah Supervisory Board (SSB) on financial, social, and shariah disclosure. The sample of this study is Islamic commercial banks in Indonesia, totaling 14 banks with an observation period of 11~years (2010-2020). The content analysis measured disclosure data and further analyzed using the fixed effect or random effect and the generalized method of moments (GMM) to overcome the endogeneity problem. We found that BOD and SSB education in finance/accounting can improve disclosure. However, the number of SSBs can reduce disclosure. The BOD and SSB play a more significant role than others in increasing shariah disclosure regarding sub-disclosure. The implication of this study is the importance of financial/accounting expertise for a BOD and SSB that will impact performance effectiveness and subsequently reduce information asymmetry.
Keywords: 650; Islamic accountability; shariah board; shariah disclosure